(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2017)
The weighted approximation errors of Meyer-Konig and Zeller operator is characterized for weights of the form w(x) = x^γ_0(1 − x)^γ_1 , where γ_0 [−1, 0], γ_1 R. Direct inequalities and strong converse inequalities of type A are proved in terms of the weighted K-functional.